Los perfiles de humedad vertical de hojas en una plantación de café - Nascimento, F.J.L. do; Tubelis, A (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
This work studies the leaf wetness vertical profiles in a coffee crop. Visual observation of wetness was done at several heights on west and east faces of plants under recent low topping condition, on the west face of plants under low topping condition and on the west face of plants under untopping condition, with north-south oriented rows The mean vertical profile of setness period duration, by dew or by rain, showed an increase from the top to the lower part of the plants in consequence of the delay on the ending moments. lnder dry soil conditions, dew formation was inhibited in the first thirty centimeters above the ground. The dew witness biggest duration occurred on west face of the plants, at 0 30 m above the ground.